Penggunaan Sistem Penjaring Informasi Hoaks dalam Menerapkan Pendidikan Anti-Hoaks bagi Guru di Masa Pandemi COVID-19 - Rahmi Ramadhani; Abdul Meizar; Dwi Ardiyanti (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
The problems experienced by partner schools are obtained through observation and interviews, among them partner teachers having difficulty in finding valid and reliable learning reference sources to use in learning materials during the online learning process. Partner teachers also often obtain links that contain untrustworthy information and are feared to be in the category of Hoax information. Based on these problems, the PKM Team conducted community partnership program activities with the aim of providing training and assistance in the implementation of Hoax information-learning system as an effort to implement anti-Hoax education for teachers during the online-based distance learning process during the COVID-19 pandemic. The number of participants in this PKM activity is as many as 28 teachers. The external target of this PKM activity is (1) there is an increase and understanding of the teachers regarding the information of the hoax that are related to social media and other online news media; (2) There is an increase in teacher's skill in using the Hoax information scorer system application that has been planned by team PKM; (3) Improvement of teachers ' skills in the process of going through the Hoax information using the application and checking the information obtained through online search; and (4) Increased teacher motivation and spirit in implementing anti-hoax education in distance learning process during pandemic COVID-19 period